Incidence and predictors of non-fatal drug overdose after release from prison among people who inject drugs in Queensland, Australia. (1st August 2015) - Winter, R.J.; Stoové, M.; Degenhardt, L.; Hellard, M.E.; Spelman, T.; Jenkinson, R.; McCarthy, D.R.; Kinner, S.A.
Highlights: We calculated the incidence of non-fatal overdose among recently released prisoners. Incidence was 27/100 person-years (PY) over 6 months post-release among people who inject drugs. The period of greatest risk was between 1 and 3 months post-release. Half of those who reported post-release overdose had no history of non-fatal overdose. By identifying the most at-risk prisoners, intervention can be better targeted. Abstract: Introduction: Release from prison is a period of elevated risk for drug-related harms, particularly among people who inject drugs (PWID). Non-fatal overdose can cause serious morbidity and predicts future fatal overdose, however neither the incidence nor the risk factors for non-fatal overdose following release from prison are well understood. Methods: Structured health-related interviews were conducted with 1051 adult prisoners in Queensland, Australia prior to release and approximately 1, 3 and 6 months post-release. Incidence of self-reported overdose in the community was calculated for PWID and all prisoners for three discrete time periods. Negative binomial regression with robust error variance was used to identify pre-release predictors of overdose among PWID. Results: The incidence of reported overdose was highest between 1 and 3 months post-release (37.8 per 100 person-years (PY) among PWID; 24.5/100 PY among all ex-prisoners). In adjusted analyses, the risk of post-release non-fatal overdose was higher for PWID who reported: being unemployed for >6 months before prison, having been removed from family as a child, at least weekly use of benzodiazepines and/or pharmaceutical opiates in the 3 months prior to prison, and ever receiving opioid substitution therapy (OST). Pre-release psychological distress and a lifetime history of mental disorder also predicted overdose, whereas risky alcohol use in the year before prison was protective. Conclusions: PWID have a high risk of overdose following release from prison. Imprisonment is an opportunity to initiate targeted preventive interventions such as OST, overdose prevention training and peer-delivered naloxone for those with a high risk profile.